Applicability of RANS, DES and LES in propeller flow noise - LU Li; XIONG Ying; WANG Rui (Zhongguo Jianchuan Yanjiu, 2017)
[Objectives] In order to study the applicability of different turbulence models in propeller flow noise prediction, taking the DTMB 4119 propeller as the research object, the numerical simulation method is used to calculate the frequency domain noise under the non-uniform flow field.[Methods] First, the hydrodynamic coefficient and surface pressure distribution coefficient are obtained via the RANS method and the accuracy of the flow field simulation is verified by comparing it with the experimental data. Next,the pulsating pressures obtained by RANS, DES and LES are considered as the sound source respectively, and combined with the acoustic boundary element method to predict the radiation noise.[Results] The results show that spectral noise is the main contributor to total noise; when noise on 1 BPF is predicted, the results obtained by the three methods are very similar, so we can use RANS to predict noise quickly; when noise on the high order of BPF needs to be predicted, the calculation results of LES are better.[Conclusions] In noise prediction, the appropriate turbulence simulation method can be selected according to the demand.